Freedom of religion: the question of apostasy for Muslims / Nor Shafahana Shaik Abdul Shukkor, Wan Mohd Farhan Zainal Abidin and Wan Teh Fatimah Wan Ismail. - Shaik Abdul Shukkor, Nor Shafahana; Zainal Abidin, Wan Mohd Farhan; Wan Ismail, Wan Teh Fatimah (2005)
The fundamental aim of this study is to examine whether Muslims in Malaysia have the right to opt out of their faith and choose another as compared to the rights given to the non-Muslims. We have done a study based on interpretation of relevant statutes and looked at the judicial decisions decided on leading cases. We have also compared and contrasted the law and cases and other doctrines involving Muslims and non-Muslims. Interviews have been conducted in order to obtain different views namely on the point of view of legal scholars and Islamic scholars. It can be said that a Muslim who wishes to apostate should go to the Syariah court to be renounced as a Muslim for the Civil court do not have the jurisdiction to do so. By this research we hope to increase awareness among the public regarding laws on apostasy in Malaysia besides proposing to have a change in the said law.